Proteinaceous necrotrophic effectors in fungal virulence - Tan, Kar-Chun; Oliver, Richard; Solomon, P.; Moffat, Caroline (CSIRO Publishing, 2010)
The host–pathogen interface can be considered as a biological battlefront. Molecules produced by both the pathogen and the host are critical factors determining the outcome of the interaction. Recent studies have revealed that an increasing number of necrotrophic fungal pathogens produce small proteinaceous effectors that are able to function as virulence factors. These molecules can cause tissue death in host plants that possess dominant sensitivity genes, leading to subsequent pathogen colonisation. Such effectors are only found in necrotrophic fungi, yet their roles in virulence are poorly understood. However, several recent key studies of necrotrophic effectors from two wheat (Triticum aestivum L.) pathogens, Pyrenophora tritici-repentis (Died.) Drechs. and Stagonospora nodorum (Berk.) Castell. & Germano, have shed light upon how these effector proteins serve to disable the host from the inside out.